2015
DOI: 10.1158/1535-7163.mct-14-0810
|View full text |Cite
|
Sign up to set email alerts
|

MGMT Expression Predicts PARP-Mediated Resistance to Temozolomide

Abstract: Melanoma and other solid cancers are frequently resistant to chemotherapies based on DNA alkylating agents such as dacarbazine and temozolomide. As a consequence, clinical responses are generally poor. Such resistance is partly due to the ability of cancer cells to use a variety of DNA repair enzymes to maintain cell viability. Particularly, the expression of MGMT has been linked to temozolomide resistance, but cotargeting MGMT has proven difficult due to dose-limiting toxicities. Here, we show that the MGMT-m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 49 publications
(67 reference statements)
3
26
0
1
Order By: Relevance
“…A preceding paper showed that MGMT-positive cancer cells strongly respond to the combination of temozolomide and PARP inhibitors (PARPi), whereas MGMT-deficient cells do not because MGMT-negative cells are primarily killed by unrepaired O6-methyl-guanine generated by low dose of temozolomide [42]. …”
Section: Resultsmentioning
confidence: 99%
“…A preceding paper showed that MGMT-positive cancer cells strongly respond to the combination of temozolomide and PARP inhibitors (PARPi), whereas MGMT-deficient cells do not because MGMT-negative cells are primarily killed by unrepaired O6-methyl-guanine generated by low dose of temozolomide [42]. …”
Section: Resultsmentioning
confidence: 99%
“…TMZ resistance has been linked to increased expression of O6-methylguanine DNA methyltransferase (MGMT) [27,28,29]. To investigate whether BIS-mediated HSF1 downregulation had an effect on MGMT, we analyzed MGMT expression using qRT-PCR in A172 and U87 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to overcome resistance to TMZ led to several approaches including direct inhibition of MGMT, blockade of abasic sites, PARP inhibition etc. [ 23 , 32 38 ]. Alternative targets to sensitize cells to TMZ such as the epidermal growth factor receptor (EGFR) have been investigated by our laboratory [ 11 , 39 – 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…N7-methylguanine and N3-methyladenine) are processed by the base excision repair machinery, in which PARP plays a central role. It has already been shown that in MGMT-proficient cells, PARP inhibition sensitized cells to TMZ [ 21 23 ] and this was believed to be due to the cytotoxic effects of unrepaired alkylated bases other than O6-methylguanine. Accordingly, given that the mechanism of cell-killing by the designed combi-molecule in BRCA1/2 depends on PARP inhibition, we also sought to determine whether the MGMT status of the cells would influence the potency of these dual PARP-DNA targeting combi-molecules.…”
Section: Introductionmentioning
confidence: 99%